Logo sebagai Komunikasi Visual dari Identitas Organisasi Difabel Tuli - Dawami, Angga Kusuma (Magenta | Official Journal STMK Trisakti, 2017)
Every entity must be known to the their community, they need a difference that can be known what is the entities it, like symbol. Logo is symbol of identity of an entity, that differentiate of other community. Deaf organization’s entity in grassroot level need a logo to diffenrentiate himself after other community entities. The problem is visual communication that a disability organization’s in a village didn’t consistent at the visual communication. It can make the brand of disability organization in village just administration, it can’t support the vision of disability in village. This paper disscuss about consistent logo can be used by deaf organization to build the bergaining position as a advocavy vision brand. For the example, Akar Tuli, PLJ, and Gerkatin. This paper use qualitative descriptive method to description how logo can be a visual communication for deaf disability organization to representation his image in their environment at village. It aim to create image himself and help the advocacy work as a vision.